Scar tissue orientation in unsutured and sutured corneal wound healing. - Melles, G R (1995)
AIMS--This study aimed to evaluate stromal wound healing morphology in short term unsutured compared with sutured corneal wounds, to define regional variation in healing within radial keratotomy wounds. METHODS--Stromal scar tissue orientation (fibroblast and collagen fibre orientation) was analysed in unsutured and adjacent sutured keratotomy wounds in monkeys, 2 to 9 weeks after surgery, using light and transmission electron microscopy. RESULTS--At 2 to 4 weeks, scar tissue orientation was transverse to the wound edge in unsutured wounds, but sagittal in sutured wounds. At 5 to 9 weeks, a reorientation of scar tissue sagittal to the wound was seen in the unsutured wounds, proceeding from the posterior to anterior wound regions. In sutured wounds, a scar tissue reorientation transverse to the wound was seen, proceeding from the anterior wound region in a posterior direction. CONCLUSIONS--Within the same cornea, sutured and unsutured wounds showed opposite patterns of healing. Sutured wounds initially healed more slowly, but obtained pseudolamellar continuity over time. In contrast, healing of unsutured wounds was characterised by an early approximation towards lamellar repair that was followed by an ineffective reorganisation of the scar. This latter pattern of healing, that may be associated with a variable weakening of the wound, may relate to the clinical findings of unpredictability and/or progression of refractive effect following radial keratotomy.